Literasi Digital Mengenai Artificial intelligence berbasis Canva dalam membentuk Skill dan Kreatif Siswa Kelas IX di SMPN 27 BATAM - rame irda sihombing; Nugroho Agustinus Manalu; Endang Olivia Situmorang; Riza Zelita Tamba; Nikita Junita Selviani Dongoran; Tio Rima Hutahaean; Junianty Lestari Sitanggang; Novita Ester Marlina Zebua; Karona Enjelina Oktavia Sihombing; Firiska Yulinata Nababan (Universitas Muhammadiyah Sidenreng Rappang, 2025)
This community service (PkM) activity was conducted by the Christian Religious Education Undergraduate Program of STT Real Batam at SMP Negeri 27 Batam, in response to the importance of digital literacy for students, particularly an understanding of Canva-based AI. The objective of this activity was to improve digital literacy, develop creativity, and equip students with practical skills in using Canva as a tool to develop their potential. The implementation method consisted of three stages: observation to map student needs and abilities, training to provide materials and hands-on practice using Canva, and evaluation to assess the results of the activity. The results of this activity showed an increase in students' understanding of Canva and their ability to produce creative digital works such as posters, brochures, and presentation assignment designs. Student enthusiasm also increased, reflected in their enthusiasm and satisfaction during the training. The conclusion of this activity is that the PkM Team successfully improved students' digital literacy and creative skills and demonstrated that the use of Canva-based AI can be an effective tool in developing the skills of a younger generation ready to face the challenges of the digital era.